PERAN PT. PERTAMINA SEBAGAI PENYEDIA PASOKAN BAHAN BAKAR MINYAK DI INDONESIA - Nelci Dolfina Japari; Ahmad Zafrullah TN.; Firman Rosjadi Djoemadi (CALYPTRA, 2018)
Petroleum has a very important role in the Indonesian economy as asource of energy for domestic economic activities. Along with the increasingeconomic development and population growth and transportation in Indonesiaresulted in increased fuel consumption (BBM), while the production of petroleumIndonesia is still very limited. This becomes a problem when dependence on non-renewable fuels such as higher fuel oil (BBM). The dependence of a country onthe import of energy will greatly affect the state of national energy security. PT.Pertamina is engaged in downstream gas station business. This study aims toanalyze PT. Pertamina as a dominant company and fuel competition in theoligopoly market to identify the advantages possessed by PT. Pertamina incompeting in the downstream business.